2013
DOI: 10.1590/s0004-282x2013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to migraine treatment does not depend on the number of prescribed medications

Abstract: ObjectiveTo compare the adherence between monotherapy and politherapy in prophylactic migraine treatment.MethodFive hundred consecutive patients with migraine from a tertiary center were retrospectively studied as to the number of preventive medications prescribed during the first visit. Adherence, defined as returning for the next consultation after 4 to 6 weeks and following the prescribed regimens, were also evaluated and compared between patients.Results71.8% were women, and 6% of the patients did not rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Indeed, mean MPR at 6 months post‐index was 0.48 for antidepressants and 0.51 for antiepileptics and beta‐blockers; these MPRs are slightly higher than in our analysis and could reflect the shorter follow‐up period. A higher adherence to migraine medication (defined as a patient taking ≥80% of the prescribed medication) of 80% has been reported in a review of medical records from a specialist center in Brazil . These patients were treated and monitored by headache specialists, which may provide some explanation for the higher adherence rate than observed in other studies, although the higher adherence rate may also reflect geographical differences in the patient population and the management of migraine …”
Section: Discussionmentioning
confidence: 84%
“…Indeed, mean MPR at 6 months post‐index was 0.48 for antidepressants and 0.51 for antiepileptics and beta‐blockers; these MPRs are slightly higher than in our analysis and could reflect the shorter follow‐up period. A higher adherence to migraine medication (defined as a patient taking ≥80% of the prescribed medication) of 80% has been reported in a review of medical records from a specialist center in Brazil . These patients were treated and monitored by headache specialists, which may provide some explanation for the higher adherence rate than observed in other studies, although the higher adherence rate may also reflect geographical differences in the patient population and the management of migraine …”
Section: Discussionmentioning
confidence: 84%
“…Based on our experience and what is available in the literature for Brazilian patients from tertiary centers, the use of preventive medications in migraineurs with high frequency headache or in chronic migraineurs is the rule …”
Section: Discussionmentioning
confidence: 99%
“…34 A study assessing adherence in individuals with migraine through self-reported medication diary found 79.6% of the sample to be adherent to preventative medication on at least 80% of days and that adherence rates did not differ between patients with monotherapy and polytherapy treatment. 35 Similarly, Krymchantowski and Tavares utilized headache diaries as a measure of adherence and reported that 76.6% of the patients were adherent to preventative regimen with 4% being nonadherent prior to the 3-month evaluation and 19.4% not returning for the 3-month follow up. 36 A longitudinal study also examining adherence to β-blockers through headache medication diaries found that 94% (85/90) of patients had taken the prescribed β-blocker on at least 25 of 30 days over a 5-month period.…”
Section: Heckman Andmentioning
confidence: 99%